Job Satisfaction Among Teachers of Private Engineering Colleges in Rayalaseema Region, Andhra Pradesh - A Study - Kumar, Kanagaluru Sai (Prabandhan: Indian Journal of Management, 2011)
The purpose of conducting this qualitative study was to explore the views of teachers working in engineering colleges with reference to the factors of job satisfaction and job dissatisfaction. These results indicate that a large number of teachers in the sample were having low job satisfaction. The study attempted to identify factors that were descriptive of the teacher likely to get satisfaction or dissatisfaction in the field of education. These factors were separated into attitude factors and demographic factors. Gender, Marital status, number of years of teaching experience, and educational qualifications were included in the demographic factors, and all other college environment and job-related factors were included in the attitude factors. The factors which lead to job satisfaction and job dissatisfaction, and their consequences were studied and were analyzed using various statistical tools. The study reveals that level of job satisfaction is different for male and females, married and unmarried teachers. The study also reveals that level of satisfaction is different for teachers of low educational qualification and the teachers of high educational qualification, as well as teachers of few years of experience and teachers of more years of experience.